OMEGA geração SA Valuation: study applied to a company with renewable electricity assets: Avaliação da OMEGA Geração SA: estudo aplicado a uma empresa com ativos de eletricidade renovável - Alves Junior, Antonio Carlos Rangel (2023)
This work aims to evaluate the value of the operating assets of generation of the company Omega Geração S.A., listed on the Brazilian stock exchange (B3), under the code OMGE3. In which, to carry out the calculation of the equity value, business analysis tools through asset Valuation (specifically the discounted cash flow approach) were used. In order to carry out the Valuation model of the assets under study, the financial statements for the years 2016 to 2020 were used to make assumptions for the projection model. With the assumptions defined, the company’s cash flows were projected for 30 years, and after that period a terminal value with no real growth was adopted. Then, future cash flows were discounted to present value by a discount rate. Modeling limitations have been fixed using information from companies’ sector that have similar assets. After the cash flow projections, and using the assumptions adopted, the equity value for the company’s operating generation assets is R$ 3,050 million. Some sensitivity simulations were carried out on the equity value. The assumptions used in the sensitivity matrix were: growth rate, cost of capital (discount rate), energy price in the spot market and cost of sales. The sensitivity matrix of the assumptions allowed the creation of a range of values for the company’s equity.